MOTIVATIONAL STRATEGIES AND ADULT EDUCATORS’ JOB SATISFACTION IN AKWA IBOM NORTH-EAST SENATORIAL DISTRICT (Unilorin Journal of Lifelong Education, 2023)
The study examined the influence of motivational strategies on adult educators’ job satisfaction in Akwa Ibom North East senatorial district. Survey research design was adopted for the study. The population for the study consisted of all the facilitators in Akwa Ibom North-East senatorial district. A simple random sampling technique was used in selecting three adult educators from two adult education centres in each Local Government Areas under the study area. This means that fifty four adult educators were selected as sample for the study. The instrument used for the study was a structured questionnaire tittled “Motivational Strategies and Adult Educators’ Job Satisfaction Questionnaire (MSAEJSQ).” The instrument was validated by an expert in measurement and evaluation in the Department of Educational Foundations, College of Education Afaha Nsit, Akwa Ibom State. Test-retest method was used to ascertain the reliability of the instrument using cronbach alpha coefficient, a reliability coefficient of 0.75 was obtained. The data collected was analyzed using chi-square statistics. The result shows that adult educators’ participation in professional development programmes significantly influenced adult educators’ job satisfaction. The result also shows that provision of material inducement significantly influenced adult educators’ job satisfaction. Based on the findings, the following recommendations were made: regular professional development programme should be organized for adult educators in Akwa Ibom North-East senatorial district; they should be encouraged to enroll in professional development programmes; adult educators should be adequately remunerated and; they should be provided with adequate instructional materials.